2022
DOI: 10.1063/5.0076855
|View full text |Cite
|
Sign up to set email alerts
|

Discharge characteristics of a gliding arc discharge in a supersonic jet air flow

Abstract: Whereas discharge characteristics of a gliding arc have previously been investigated in a low-speed subsonic flow without considering the effect of shock waves and extremely high turbulence, we here studied an important physical feature of the gliding arc in a supersonic flow that generates complex shock waves and extremely high turbulence. The gliding arc in a 1.2 Mach supersonic jet air flow is investigated by high-speed imaging, schlieren imaging, electrical measurements, and the large eddy simulation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Correspondingly, the ordinary discharge, which was characterized by a long duration and an amplitude of hundreds of milliamperes in the currents (like the currents in Figure 5a), was recognized as a glow-type discharge. The experimental result was in accordance with [27,29].…”
Section: Characteristics Of Gliding Arc Plasma Discharge In Stable Fl...supporting
confidence: 83%
See 1 more Smart Citation
“…Correspondingly, the ordinary discharge, which was characterized by a long duration and an amplitude of hundreds of milliamperes in the currents (like the currents in Figure 5a), was recognized as a glow-type discharge. The experimental result was in accordance with [27,29].…”
Section: Characteristics Of Gliding Arc Plasma Discharge In Stable Fl...supporting
confidence: 83%
“…Many studies have confirmed that the air flow rates have a great influence on gliding arc plasma [26,27]. In this experiment, the current, voltage, and power waveforms were measured with different flow rates.…”
Section: Characteristics Of Gliding Arc Plasma Discharge In Stable Fl...mentioning
confidence: 90%
“…The improvement type refers to adding new techniques for existing thermal plasma, such as realizing a warm arc or adding a highfrequency source. In this solution, Czernichowski et al [15] promoted the concept of a sliding arc, and then Sun et al [16], Lu et al [17], Zhu et al [18], Feng et al [19] and others applied it to a variety of electrodes, such as blade electrodes, rotating electrodes, Raval electrodes and so on, and explored the combination of sliding arc and other devices. This type of method is usually applied to some endothermic reaction applications (such as fuel reforming), and its efficiency is usually about 50% (the efficiency is defined as the ratio of the reaction enthalpy and actual energy expenses).…”
Section: Introductionmentioning
confidence: 99%